Robotic Total Gastrectomy With Intracorporeal Robot-Sewn Anastomosis: A Novel Approach Adopting the Double-Loop Reconstruction Method. Issue 49 (December 2015) - Parisi, Amilcare; Ricci, Francesco; Trastulli, Stefano; Cirocchi, Roberto; Gemini, Alessandro; Grassi, Veronica; Corsi, Alessia; Renzi, Claudio; De Santis, Francesco; Petrina, Adolfo; Pironi, Daniele; D'Andrea, Vito; et al.
Abstract : Abstract: Gastric cancer constitutes a major health problem. Robotic surgery has been progressively developed in this field. Although the feasibility of robotic procedures has been demonstrated, there are unresolved aspects being debated, including the reproducibility of intracorporeal in place of extracorporeal anastomosis. Difficulties of traditional laparoscopy have been described and there are well-known advantages of robotic systems, but few articles in literature describe a full robotic execution of the reconstructive phase while others do not give a thorough explanation how this phase was run. A new reconstructive approach, not yet described in literature, was recently adopted at our Center. Robotic total gastrectomy with D2 lymphadenectomy and a so-called "double-loop" reconstruction method with intracorporeal robot-sewn anastomosis (Parisi's technique) was performed in all reported cases. Preoperative, intraoperative, and postoperative data were collected and a technical note was documented. All tumors were located at the upper third of the stomach, and no conversions or intraoperative complications occurred. Histopathological analysis showed R0 resection obtained in all specimens. Hospital stay was regular in all patients and discharge was recommended starting from the 4th postoperative day. No major postoperative complications or reoperations occurred. Reconstruction of the digestive tract after total gastrectomy is one of the main areas of surgical research in the treatment of gastric cancer and in the field of minimally invasive surgery. The double-loop method is a valid simplification of the traditional technique of construction of the Roux-limb that could increase the feasibility and safety in performing a full hand-sewn intracorporeal reconstruction and it appears to fit the characteristics of the robotic system thus obtaining excellent postoperative clinical outcomes.